Tirukkīḻvēḷūr - Vīrarākava Mutaliyār, 17th cent (T.N.D.A. pub., 1981)
Verse work in ulā, Tamil minor literary form, in praise of Siva, Hindu deity, enshrined at Tirukkīḻvēlūr, near Tiruvarur, Tamil Nadu.